On the unique solvability of a nonlinear nonlocal boundary-value problem for systems of second order functional differential equations - Dilna, N.Z. (Нелінійні коливання, 2016)
We establish some optimal, in a sense, general conditions sufficient for the unique solvability of the boundary-value problem for a system of nonlinear second order functional differential equations. The class of equations considered covers, in particular, neutral type equations. Concrete example is presented to illustrate the general theory. Встановлено новi, в певному сенсi, оптимальнi умови, достатнi для однозначної розв’язностi крайової задачi для систем нелiнiйних функцiонально-диференцiальних рiвнянь другого порядку. Клас рiвнянь, що дослiджувалися, може частково мiстити в собi рiвняння нейтрального типу. Наведено приклад, що демонструє отриманi результати.